Pengembangan Instrumen Evaluasi Afektif Mata Pelajaran Ips-Ekonomi di Sekolah Menengah Pertama - Endang Sri Suyati; Iin Nurbudiyani; Suniati Suniati (Anterior Jurnal, 2016)
This study aims to develop an affective evaluation instrument for junior high school students. The research was conducted from November to December 2014 on all of the public and private junior high school in Palangka Raya City. The population of this study was all students in second grade of state and private junior high school in Palangka Raya city spread over 10 (ten) state and private junior high school. Samples were taken by purposive sampling , that is by taking into several considerations of school quality (good, moderate, or less), the type of school (public and private) so it could described a variety of populations . In this study, each category is taken 2 (two) for each public and private schools. So that there are 6 (six) schools as the research sample. In this study are drawn 100 students as the subject of test instruments The instrument tried out was questionnaire by using Likert scale models with 5 (five) options. Try out done twice in difference time in two week. After taken try out of the tests twice it showed that, from 40 items of questionnaire there are 25 valid item of questionnaire and 15 items didn’t valid with the average price r ≥ 0,4. While the reliability test also has taken to the valid items which got r11 at current prices amounted to 0.9089